The Canonical Classical Model of Political Economy - Samuelson, Paul A.; Smith, Adam; Ricardo, David; Mill, John Stuart (Journal of Economic Literature, 2016)
Adam Smith, David Ricardo, Thomas Robert Malthus, and John Stuart Mill shared in common essentially one dynamic model of equilibrium, growth, and distribution. When the limitation of land and natural resources is added to the model of Karl Marx, he also ends up with this same canonical classical model. In its present version the model is stripped down to its minimal essentials. For brevity I employ modern mathematical tools, but only to characterize in modern terms the relations that were actually common to all these writers. The reader should of course be warned that any simple codification of the classical economists' discursive writings must be an oversimplification: in some of their passages they qualify what they have written elsewhere; in some they provide negations and contradictions. Not a few of the stereotypes about the classical writers are, to paraphrase Voltaire, myths agreedupon by later commentators-distortions that both improve and libel the originals. The relevant object of study for a modern scholar is the corpus of original texts and the commentaries on them, the latter not being genuinely of less interest than the former once we have succeeded in telling them apart. To the fascinating question of whether classical political economy does, or can be made to, offer an alternative paradigm –in the sense of Thomas Kuhn [11, 1962]-to modern mainstream economics, the present investigation provides an instructive answer. So to speak, within every classical economist there is to be discerned a modern economist trying to be born. A Ricardo or Mill did not so much replace supply and demand by quite different mechanisms but rather sought to be able to say something significant and limiting about their properties, quite in the same way that we moderns endeavor to do. I describe and analyze here the basic classical model in its essential form.